Cerebellar degeneration in dominantly inherited spastic paraplegia. Issue 2 (February 1985) - Scholtz, C L; Swash, M
Abstract : The clinical features of five affected members in three generations of a family with dominantly inherited Strumpell's spastic paraplegia are described, together with the pathological findings in two cases. The late presentation and slow progression of the disease encompass features of the types I and II of other authors illustrating the heterogeneous expression of the disorder. Cerebellar involvement was evident clinically and pathologically.